The communication package to improve drug adherence behavior among vivax malaria patients without G6PD deficiency for malaria elimination along international borders, Northern Thailand - ขันธิกุล, นารถลดา; แซ่เจ็ง, อังคณา; ไชยวัณณ์, จินตนา; บุญอินทร์, พัชรินทร์; อรุโณทอง, สุรเชษฐ์; สุดาทิพย์, ประยุทธ (Disease Control Journal, 2018)
A communication package for malaria Plasmodium vivax patient’s treatment is urgently needed at the first step in malaria elimination program. The objectives of this quasi experimental research were to compare knowledge and perception before and after implementation of a novel tool package, a vivax malaria education program toward the patients and, secondly, to measure levels of patients’ ability of drug adherence, behaviors of taking drugs and satisfaction after receiving this intervention. The research was conducted in public health service units in Mae Hong Son, Chiang Mai and Chiang Rai provinces between January and March 2015. Vivax Malaria patients were screened for G6PD deficiency using Fluorescence spot test (FST), only 36 normal G6PD patients were enrolled after a written informed consent had been obtained for voluntary participation and completion of research procedures. Results showed that the majority of the patients 83.3% (30 out of 36) presented their drug taking behavior with correction, completion and adherence to malaria treatment according to the National Malaria Treatment Guidelines. After the implementation, average scores of knowledge and perception were significantly higher than those before the implementation (p<0.05). Following the implementation, the participants became acutely aware of their ability to comply with drug adherence. Besides that the participants had a high level of satisfaction from malaria clinic services units. The overall feedback from this study is beneficial for public health officers as it could help them be cognizant of socio-cultural factors in developing an innovative intervention program for vivax malaria patients concerning adherence to the drug prescriptions.